Health information needs and It’s sources among rural dwellers in Egbedore Local Government areas of State of Osun, Nigeria (2019)
The study investigated the health information needs and its sources among rural dwellers in Egbedore local government areas of the state of Osun. The study employed a survey and observation methods to collect information from rural dwellers, findings from the data analyzed revealed the health information needs such as immunization, family planning, pre-natal, personal hygiene, malaria, clean water supply and post-natal. Sources of health information to includes; radio, town crier, health officers, church, mosque, posters, ministry of health information van, conversation, television and newspapers. The result of the research indicated that radio, town crier, health officers and ministry of health van were their most preferred sources of information. It was indicated that library performed no roles in information dissemination in rural areas of Egbedore as a result of non-availability of library and its facilities in the area. Recommendation was made on how the library can assist in provision of health information to rural dwellers.